Magnetic Nanoparticles Enhance Pore Blockage-Based Electrochemical Detection of a Wound Biomarker - Rajeev, Gayathri; Cowin, Allison J.; Voelcker, Nicolas H.; Prieto Simon, Beatriz (Frontiers in Chemistry, 2019)
A novel pore blockage-based electrochemical immunosensor based on the combination of 100 nm-magnetic nanoparticles (MNPs), as signal enhancers, and 200 nm-pore diameter nanoporous anodic alumina (NAA) membranes, as sensing platform, is reported. A peptide conjugate mimicking flightless I (Flii), a wound healing biomarker, was chosen as target analyte. The sensing platform consists of an anti-Flii antibody (Ab1)-modified NAA membrane attached onto a gold electrode. Anti-KLH antibody (Ab2)-modified MNPs (MNP-Ab2) were used to selectively capture the Flii peptide conjugate in solution. Sensing was based on pore blockage of the Ab1-modified NAA membrane caused upon specific binding of the MNP-Ab2-analyte complex. The degree of pore blockage, and thus the concentration of the Flii peptide conjugate in the sample, was measured as a reduction in the oxidation current of a redox species ([Fe(CN)6]4-) added in solution. We demonstrated that pore blockage is drastically enhanced by applying an external magnetic field at the membrane backside to facilitate access of the MNP-Ab2-analyte complex into the pores, and thus ensure its availability to bind to the Ab1-modified NAA membrane. Combining the pore blockage-based electrochemical magnetoimmunosensor with an externally applied magnetic field, a limit of detection (LOD) of 0.5 ng/ml of Flii peptide conjugate was achieved, while sensing in the absence of magnetic field could only attain a LOD of 1.2 µg/ml. The developed sensing strategy is envisaged as a powerful solution for the ultra-sensitive detection of an analyte of interest present in a complex matrix.